Effectiveness of Endoscopic Treatment for Gastrointestinal Neuroendocrine Tumors: A Retrospective Study. Issue 15 (April 2016) - Sun, Weili; Wu, Siyuan; Han, Xiao; Yang, Chuanhua
Abstract : Abstract: Several recent studies have explored efficacy and safety of different endoscopic treatments for gastrointestinal neuroendocrine tumors (GI-NETs). However, there is no definitive consensus regarding the best endoscopic approach for GI-NETs treatment. Therefore, the present study was conducted to investigate the application of various endoscopic techniques for the treatment of GI-NETs according to the previous conclusions and to summarize the optimal endoscopic modalities for GI-NETs. Ninety-eight patients with 100 GI-NETs removed by endoscopic therapies were reviewed. The pathological complete resection rate (PCRR), complication, local recurrence, and factors possibly associated with the pathological complete resection were analyzed. Twenty-two patients were treated by conventional polypectomy (including 6 cold biopsy forceps polypectomy and 16 snare polypectomy with electrocauterization), 41 by endoscopic mucosal resection (EMR), and 35 by endoscopic submucosal dissection (ESD). The PCRRs of conventional polypectomy, EMR, and ESD were 86.4%, 75.6%, and 85.7%, respectively. Sixteen GI-NETs that had a polypoid appearance, with a mean tumor size of 5.2 mm, were removed by snare polypectomy (PCRR 93.8%). The complication rates of conventional polypectomy, EMR, and ESD were 0.0% (0/22), 2.4% (1/41), and 2.9% (1/35), respectively. There were 2 local recurrences after cold biopsy forceps polypectomy treatment and no local recurrences in the EMR and ESD groups ( P = 0.049). The results showed that PCRR was only associated with the depth of invasion ( P = 0.038). Endoscopic resection of GI-NETs is safe and effective in properly selected patients. For submucosal GI-NETs, ESD was a feasible modality, with a higher PCRR compared with EMR. For ⩽5 mm polypoid-like NETs, snare polypectomy with electrocauterization was a simple procedure with a high PCRR.